2016
DOI: 10.1016/j.metabol.2016.09.004
|View full text |Cite
|
Sign up to set email alerts
|

Perilipin 1 binds to aquaporin 7 in human adipocytes and controls its mobility via protein kinase A mediated phosphorylation

Abstract: Accumulating evidence suggests that dysregulated glycerol metabolism contributes to the pathophysiology of obesity and type 2 diabetes. Glycerol efflux from adipocytes is regulated by the aquaglyceroporin AQP7, which is translocated upon hormone stimulation. Here, we propose a molecular mechanism where the AQP7 mobility in adipocytes is dependent on perilipin 1 and protein kinase A. Biochemical analyses combined with ex vivo studies in human primary adipocytes, demonstrate that perilipin 1 binds to AQP7, and t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
29
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 28 publications
(32 citation statements)
references
References 37 publications
(51 reference statements)
1
29
1
Order By: Relevance
“…In adipocytes under basal conditions (presence of insulin), standard deviation projections from 3D z-stacks show topologically distinct domains enriched in PLIN1 (Fig. 1a ), as per our previously published results 12 . Upon stimulation with the β-adrenergic receptor agonist isoprenaline, the PLIN1 domains are abolished and instead a more homogenous PLIN1 stain is observed (Fig.…”
Section: Resultssupporting
confidence: 89%
See 2 more Smart Citations
“…In adipocytes under basal conditions (presence of insulin), standard deviation projections from 3D z-stacks show topologically distinct domains enriched in PLIN1 (Fig. 1a ), as per our previously published results 12 . Upon stimulation with the β-adrenergic receptor agonist isoprenaline, the PLIN1 domains are abolished and instead a more homogenous PLIN1 stain is observed (Fig.…”
Section: Resultssupporting
confidence: 89%
“…These functions of the lipolytic scaffold require a closely associated and dynamic interplay of perilipins with lipid substrates and/or other lipid droplet-associated proteins that remain undetermined 11 . Along these lines, we previously identified the glycerol channel AQP7, as a novel interaction partner of PLIN1 in human primary adipocytes 12 . In addition, confocal microscopy images revealed that PLIN1 forms distinct domains on the lipid droplet surface during insulin stimulation, whereas under lipolytic conditions the distinct protein segregation is abolished resulting in a more homogenous staining pattern 12 .…”
Section: Introductionmentioning
confidence: 87%
See 1 more Smart Citation
“…Recently, in vitro studies in human primary adipocytes has suggested that, in response to insulin stimulation, AQP7 localization to the plasma membrane is prevented by binding to the lipid droplet (LD)-associated protein perilipin 1 (PLIN1). In response to isoprenaline, the binding of AQP7 to PLIN1 is inhibited by phosphorylation of the cytosolic N-terminus of human AQP7 at S10/T11 by protein kinase A, thus allowing the translocation of the protein to the plasma membrane [7]. Interestingly, this phosphorylation site resides at the initial part of the AQP7 N-terminus, which is only found in human AQP7 [8].…”
Section: Adipose Tissuementioning
confidence: 99%
“…The rat aqp7 gene encodes a 269 amino acid (aa) protein, with a predicted molecular mass of 28.9 kDa [6]. The deduced amino acid sequence of human AQP7 (hAQP7) is 342 aa long [7,8], while in mice (mAQP7), the protein is 303 aa in length [8]. The hAQP7 sequence is 67% identical to mAQP7, and both share 68% and 79% sequence homology with rat AQP7 (rAQP7), respectively.…”
Section: Introductionmentioning
confidence: 99%